Digital Payment Adoption and Financial Management Efficiency of Culinary MSMES: A Study of QRIS Users in Bandung, Indonesia - Sopian, Erik; Nugraha, Nugraha; Waspada, Ika Putera; Sari, Maya (Journal of Social Work and Science Education, 2026)
This study examines the effect of digital payment adoption on the financial management efficiency of culinary micro, small, and medium enterprises (MSMEs) using the Quick Response Code Indonesian Standard (QRIS) in Bandung, Indonesia. Amid rapid digitalization, many MSMEs continue to face challenges in transaction recording and cash flow management, despite the potential of digital payment systems to automate and streamline these processes. A quantitative approach with a descriptive-causal design was employed. Data were collected through a Likert-scale questionnaire (1–5) administered to 100 culinary MSME owners who actively used QRIS for at least three months, selected through purposive sampling. Data analysis included validity and reliability testing, classical assumption tests (normality, linearity, heteroscedasticity), and simple linear regression. The results show that digital payment adoption has a positive and significant effect on financial management efficiency (β = 0.571, t = 6.884, p < 0.001). The coefficient of determination (R² = 0.326) indicates that 32.6% of the variance in financial management efficiency is explained by digital payment adoption. The use of QRIS automates transaction records, enhances data accuracy, minimizes manual errors, and simplifies reconciliation. Two items (ease of use and frequency of use) were dropped due to a ceiling effect, as active users exhibited homogeneous positive perceptions. This study concludes that QRIS adoption plays a meaningful role in improving MSME financial governance. Practical implications include the need for enhanced digital literacy training for MSME actors and integrated policy design by regulators. Limitations include the cross-sectional design and moderate explanatory power; future research should incorporate mediating variables such as digital financial literacy.